Pengembangan Buku Saku Digital Berbasis STEM Berbantuan Appypie: Studi Terhadap Kemampuan Berpikir Kreatif Siswa - Komarudin Komarudin; Gusti Ayu Farah Nabilla; Saiful Bahri; Laila Puspita; Muhammad Afandi (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2022)
This study aims to test the feasibility, attractiveness, and effectiveness of learning media in the form of STEM-based digital pocket books assisted by Appypie on students’ creative thinking skills on triangle material. Research and development (R&D) in this study uses the ADDIE model with 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The data collection techniques used were interviews, questionnaires, and tests. Data collection instruments in this study include student needs questionnaires, interview sheets, expert validation questionnaires, student response questionnaires, and tests. The data analysis techniques used are expert validation data analysis, and student response data analysis. Based on the results of the validation test, an average score of 3.63 from material experts and 3.70 from media experts was obtained (feasible to use). The attractiveness response that has been carried out in small and large class tests obtained an average score of 3.57 (very interesting) and 3.80 (very interesting), respectively. The effectiveness test on the use of learning media developed in this study could not be carried out due to the constraints of the Covid-19 pandemic, so this research was limited to the development stage. It can be concluded that the STEM-based digital pocket book assisted by Appypie on students' creative thinking skills on triangle material is feasible and interesting to use in the learning process.This study aims to test the feasibility, attractiveness, and effectiveness of learning media in the form of STEM-based digital pocket books assisted by Appypie on students’ creative thinking skills on triangle material. Research and development (R&D) in this study uses the ADDIE model with 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The data collection techniques used were interviews, questionnaires, and tests. Data collection instruments in this study include student needs questionnaires, interview sheets, expert validation questionnaires, student response questionnaires, and tests. The data analysis techniques used are expert validation data analysis, and student response data analysis. Based on the results of the validation test, an average score of 3.63 from material experts and 3.70 from media experts was obtained (feasible to use). The attractiveness response that has been carried out in small and large class tests obtained an average score of 3.57 (very interesting) and 3.80 (very interesting), respectively. The effectiveness test on the use of learning media developed in this study could not be carried out due to the constraints of the Covid-19 pandemic, so this research was limited to the development stage. It can be concluded that the STEM-based digital pocket book assisted by Appypie on students' creative thinking skills on triangle material is feasible and interesting to use in the learning process.